2020
DOI: 10.4236/ojog.2020.1010016
|View full text |Cite
|
Sign up to set email alerts
|

Oil Spills, Gas Flaring and Adverse Pregnancy Outcomes: A Systematic Review

Abstract: Oil spills and gas flaring are major environmental problems and pose major source of adverse health outcomes to communities hosting oil wells and natural gas. As oil is spilt and gas is flared; air, soil and water in affected communities are polluted. Due to this, members of these communities are exposed to higher health risks. One vulnerable group that is usually affected in this regard is pregnant women. This systematic review identified and reviewed past studies on oil pollution and different types of pregn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Despite these facts and figures, there is a huge dearth of studies on the linkage of health outcomes (in terms of life expectancy) with environmental pollution and economic variables like FDI and agricultural output. Most of the studies done in Nigeria have focused solely on oil spill and gas flaring pollutants in the Niger Delta region (Giwa et al, 2019;Nriagu et al, 2016;Oghenetega et al, 2019;Osuoha and Fakutiju, 2017;Seiyaboh and Izah, 2017), and studies outside the Niger Delta regions are mainly micro-based (Aliyu et al, 2019;Aliyu and Botai, 2018;Ogbonna et al, 2018;Oguntoke et al, 2019;Olalekan et al, 2018;Yakubu, 2018). This study, therefore, improves on earlier studies by estimating the direct and indirect effects of air pollution on life expectancy on a macro scale.…”
Section: Carbon Emission and Life Expectancy Nexusmentioning
confidence: 78%
See 1 more Smart Citation
“…Despite these facts and figures, there is a huge dearth of studies on the linkage of health outcomes (in terms of life expectancy) with environmental pollution and economic variables like FDI and agricultural output. Most of the studies done in Nigeria have focused solely on oil spill and gas flaring pollutants in the Niger Delta region (Giwa et al, 2019;Nriagu et al, 2016;Oghenetega et al, 2019;Osuoha and Fakutiju, 2017;Seiyaboh and Izah, 2017), and studies outside the Niger Delta regions are mainly micro-based (Aliyu et al, 2019;Aliyu and Botai, 2018;Ogbonna et al, 2018;Oguntoke et al, 2019;Olalekan et al, 2018;Yakubu, 2018). This study, therefore, improves on earlier studies by estimating the direct and indirect effects of air pollution on life expectancy on a macro scale.…”
Section: Carbon Emission and Life Expectancy Nexusmentioning
confidence: 78%
“…, 2019; Nriagu et al. , 2016; Oghenetega et al. , 2019; Osuoha and Fakutiju, 2017; Seiyaboh and Izah, 2017), and studies outside the Niger Delta regions are mainly micro-based (Aliyu et al.…”
Section: Introductionmentioning
confidence: 99%
“…Environmental pollutants such as volatile organic compounds (VOCs), heavy metals, polycyclic aromatic hydrocarbons (PAHs) are released when oil is spilt, and gas flared [1]. Several authors have reported that living in areas polluted by oil have adverse effects on human health [5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Despite these ironical and worrisome statistics, there is a huge dearth of studies on the relationship between air pollution and life expectancy in Nigeria. Again, most of the studies done in Nigeria have focused specifically on oil spill and gas flaring pollutants in the Niger Delta region using survey research design, without controlling for economic variables like FDI and agricultural output (Aliyu et al, 2019;Aliyu and Botai, 2018;Giwa et al, 2019;Nriagu et al, 2016;Ogbonna et al, 2018;Oghenetega et al, 2019;Oguntoke et al, 2019;Osuoha and Fakutiju, 2017;Seiyaboh and Izah, 2017). This study, therefore improves on earlier studies by employing the dynamic vector autoregression modeling to estimate the relationship between air pollution and life expectancy, and extended the Grossman's health stock theory with the help of pollution haven hypothesis (PHH) and the environmental Kuznets curve (EKC).…”
Section: Introductionmentioning
confidence: 99%